Clinical updates of JAK inhibitors in cutaneous granulomatous diseases - Gu, Jiaxu; He, Xinglin; Lu, Bingcheng; Wang, Jieyi; Chen, Kexin; Wang, Qiaofen; Jian, Xingling; Huang, Cong; Yu, Bo (Frontiers in Immunology, 2025)
Cutaneous granulomatous diseases, characterized by persistent granuloma formation, often exhibit chronic and relapsing courses that are challenging to manage with conventional therapies. The Janus kinase (JAK)–signal transducer and activator of transcription (STAT) pathway plays a central role in mediating key cytokines involved in granuloma initiation and maintenance, such as IFN-γ, IL-6, IL-12, and IL-23. JAK inhibitors, by targeting this pathway, offer a promising therapeutic strategy for refractory cases. This review synthesizes current evidence supporting the efficacy of JAK inhibitors—including tofacitinib, ruxolitinib, baricitinib, upadacitinib, and abrocitinib—in conditions such as sarcoidosis, granuloma annulare, granulomatous rosacea, and adverse reactions to cosmetic injectables. Clinical studies and case reports have demonstrated that JAK inhibitors significantly improve lesion outcomes and effectively control symptoms in these conditions, highlighting their potential as targeted treatments. However, further large-scale trials are needed to establish optimal dosing, long-term safety, and predictive biomarkers for personalized therapy.